Implementas Mesin Pengering “Cabinet Dryer” pada UMKM “RISQI” Desa Curah Cottok, Kapongan, Situbondo, Jawa Timur - andrew joewono; Adriana Anteng Anggorowati; Dyna Rachmawati; Lorensius Anang Setiyo Waloyo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
The onion crackers produced by Mrs. Tutik are a micro-scale business in the cracker industry. This business has been established since 2016, Mrs. Tutik is an entrepreneur who has a desire to advance her business. However, they have not used more advanced (manual) production equipment (machines). Until now, Mrs. Tutik's crackers are only sold in the vicinity of the village, and village markets which are in the same area as Kapongan District.The food consumption pattern of the East Java population cannot be separated from crackers, which creates a large market opportunity for the